Differential mechanisms of action are involved in chlorpyrifos effects in estrogen-dependent or -independent breast cancer cells exposed to low or high concentrations of the pesticide - Ventura, Clara (2012)
It has reported that many environmental compounds may display estrogenic actions and these findings led to researchers to associate breast cancer risk with the use of some pesticides. The aim of this work was to investigate the effect of chlorpyrifos (CPF) on cell proliferation and the ERα-dependence of this action employing MCF-7 and MDA-MB-231 breast cancer cell lines. We have also analyzed CPF action on the cell cycle distribution and the cyclins that are implicated in G1-S and intra-S checkpoints. Finally, the action on cell death and ROS production were studied. We demonstrated the ability of CPF 0.05 μM to induce cell proliferation through ERα in hormone-dependent breast cancer cells. In contrast, CPF 50 μM induces intra-S arrest modifying checkpoints proteins, through a mechanism that may involve changes in redox balance in MCF-7. In MDA-MB-231, we have found that CPF 50 μM produces an arrest in G2/M phase which could be related to the capacity of the pesticide for binding to tubulin sites altering microtubules polymerization. Altogether, our results provide new evidences on the action of the pesticide CPF as an environmental breast cancer risk factor due to the effects that causes on the mechanisms that modulate breast cell proliferation.